If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -8c = 25 Solving 3 + -8c = 25 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -8c = 25 + -3 Combine like terms: 3 + -3 = 0 0 + -8c = 25 + -3 -8c = 25 + -3 Combine like terms: 25 + -3 = 22 -8c = 22 Divide each side by '-8'. c = -2.75 Simplifying c = -2.75
| 6x-(-6)= | | 2a/3+8/9=4 | | 12-2m=-18 | | 4x-14=-82 | | 40=50*(1-r) | | 2-6x=-4x+1 | | 8x-4=x+10 | | 2p=-256 | | 30+6x=5x | | x+439=(x-58)2 | | 2(m+4)=m+2 | | 78+r=-76 | | 151(57457+9)+9252=1 | | x=x^2-x-12 | | 6(x+3)=10 | | ln(x+2)+ln(x)=ln(x+12) | | 0.50x+0.35(50)=47.5 | | 6(x-3)=10 | | -12/9-30/-12= | | 3f+15=51 | | -2.8=w | | 400*400= | | x*x+1200=2x*2x | | R(6-s-t)+6p(6-s-t)= | | -2c+2=5c | | 3=14+2x | | 6x+(x+1)=5(x+1) | | 4x^2-5x+9=2x+6 | | x+x+x+x=30 | | -(-n)=1 | | y=7x-53 | | 7(m-n)+p(m-n)= |